The Gambia : A Look at Agriculture - Mungai, Rose (World Bank, Washington, DC, 2020)
Agriculture is a vital sector in the Gambia. It accounts for about 17.8 percent of gross domestic product (GDP), ranking behind the services sector, which recorded 68.8 percent of GDP. Employment in agriculture appears to be mainly driven by women, who are more likely to engage than men. In general, more than two-thirds of Gambians reside in rural areas and derive their livelihoods from agriculture and related activities. Therefore, the sector is a prime area for investment to achieve poverty reduction as stated in the country’s vision 2020 document. Agriculture is an important source of income for households, behind wages and salaries and petty trading. The agriculture sector plays an important role in ending hunger, malnutrition, and extreme poverty. In rural areas, the agriculture sector’s role in poverty reduction and shared prosperity policies is particularly important.